Limited use of opioid prescribing guidelines in Dutch emergency departments: results of a nationwide survey - Nicole Kraaijvanger; Cees Kramers; Albert Dahan; Arnt F. A. Schellekens (International Journal of Emergency Medicine)
Abstract Background In recent years, the Netherlands has experienced a notable increase in opioid prescriptions and associated fatalities. Emergency department (ED) patients exhibit relatively high rates of opioid use (15%) and misuse (23% of patients who present to the ED and use prescription opioids test positive for misuse). To mitigate opioid-related harm, the American College of Emergency Physicians (ACEP) advocates for the use of non-opioid analgesics and minimal opioid prescriptions. In the Netherlands, the Society for Anesthesiology has issued a guideline for appropriate opioid use, which are also relevant to EDs. However, the extent of implementation in EDs remains unclear. This study utilized an online survey to assess the implementation of opioid-prescribing guidelines in Dutch EDs. Chief medical officers from various EDs across the Netherlands were invited via email to complete questionnaires. These questionnaires gathered general information about the EDs, details on the application of opioid-prescribing guidelines, management of problematic opioid use, and specifics of the guidelines in practice. Results Questionnaires were completed by chief medical officers from 33 Dutch EDs, yielding a 52.4% response rate. Nineteen EDs (57.6%) used guidelines for opioid prescribing, predominantly local protocols, with only two of them (10.5%) using the national guideline. The guidelines varied in content, with 68.4% advising on specific opioids (mainly preferring oxycodone) and dosage, and in 63.2% giving advice on prescription duration (typically 3–7 days). Patient education with opioid prescriptions was specified in the guidelines at 57.9% (11/19) of EDs, with brochures provided at 17.6% (6/19) of EDs. The primary focus of patient education was on adverse effects, with addiction risks mentioned at 36.4% (4/11) EDs. Conclusions This study reveals significant variability and gaps in opioid prescribing guidelines across Dutch EDs. Compared to US guidelines, Dutch practices are less cautious, highlighting the need for improvement. This study underscores the necessity for a Dutch guideline tailored for EDs to manage opioid prescriptions and problematic opioid use.